Awareness Regarding Preconception Care among Reproductive Age Women in a Community - Thapa, Ranju; Dangol, Bhuwan Kumari (Journal of Nursing Education of Nepal, 2024)
Introduction: Preconception Care is critical component between planning pregnancy to conception. It aims at successful pregnancy and its outcome. It focuses on health promotion, risk factor assessment and intervention. The objective of this study was to find out the awareness regarding preconception care among reproductive age women in a community.Methods: A descriptive cross-sectional study was conducted among 85 women of reproductive age in ward no 4 of Tokha municipality, samples were selected using the non-probability convenience sampling technique. A self-developed, semi structured interview schedule was used for data collection by in person interview method. Data was analyzed by using SPSS version 16. Descriptive statistics frequency, mean, mode, median, range, percentage, and standard deviation were used to describe socio-demographic variables and level of awareness and inferential statistics Chi-square and fisher exact test were used to measure the association between level of awareness and selected variables.Results: The findings revealed that nearly half (44.7%) respondents had adequate awareness, 43.5% had moderate awareness, and 11.8% had low awareness regarding preconception care. The level of awareness was associated with husbands’ education level and history of abortion.Conclusion: Less than half women of reproductive age have adequate awareness regarding preconception care, with more awareness on risk factor assessment and less awareness on the area of intervention and management. Therefore, it would be preferable to implement formal and informal education and awareness programs on many aspects of preconception care in the community to promote awareness.
Keywords: Awareness; preconception care; reproductive age; women